Pedestrian Movement Evaluation: Amman, Jordan - Tomah (Maayah), Ayman Najib (project baikal, 2024)
This study examines walkability in Amman’s residential areas, focusing on pedestrian safety and satisfaction. Three neighborhoods underwent surveys and focus group discussions. Statistical methods were used for data evaluation, while on-site assessments and photographic documentation complemented quantitative data. Main pedestrian issues included inadequate infrastructure and lack of traffic enforcement. Residents showed positive attitudes towards walkability but expressed concerns about safety and convenience. The findings stress the need for improved design, planning laws, and pedestrian infrastructure. These results serve as a valuable resource for policymakers and urban planners facing similar challenges.